Understanding Nursing Knowledge of Continence Care and Bladder Scanner Use in Long-Term Care: An Evaluation Study - Tracy M. Christianson RN, BSN, MN, DHEd; Tracy J. Hoot RN, BScN, MScN, DHEd; Melanie Todd RN, BSN, MPH (Gerontology and Geriatric Medicine, 2021)
Because urinary continence is an essential indicator for quality of life for older adults in long-term care, it is important to accurately assess and treat those at risk for incontinence. This evaluation study was to increase understanding of the issues related to the implementation of bladder scanners while exploring nursing staff knowledge about continence care of older adults in long-term care settings. Using a mixed-methods design, nursing care staff (RN, LPN, Care Aide) at six long-term care homes completed a bladder care knowledge survey and participated in focus group discussions to explore continence care knowledge and use of bladder scanners to manage continence issues. Twenty-eight nursing care staff participated; findings showed continence care knowledge varied by profession, and the use of portable bladder scanners is affected by knowledge, training, and scopes of practice. Going forward, exploring scopes of practice and education are needed for effective assessment, management, and treatment of continence.